동압베어링의 그르브 가공용 양방향 펄스 파워 전해가공시스템 개발 - 李龍根(Yong-Geun Lee) (전기학회 논문지 P권, 54(4), 2005)
This paper presents a bidirectional pulse power electrochemical etching system for groove manufacturing of the dynamic bearings. To manufacture the dynamic bearing for the groove, it is very important to consider the depth and roughness. If the precision of the groove is not exact, we can not get the desirable performance for the target of the dynamic bearing. To make the groove of bearing precise, we propose the method of electrochemical etching system. In order to design the depth and roughness exactly, the bidirectional pulse power converter is proposed. With the bidirectional pulse power converter, we obtain the condition and the parameters of converter such as frequency, duty ratio, time, temperature, velocity, pressure and so on. In this paper, we get the experimental results to verify the precise groove manufacturing.